Analyzing national policy styles empirically using the Sustainable Governance Indicators (SGI): insights into long‐term patterns of policy‐making. Issue 2 (25th April 2022) - Tosun, Jale; Howlett, Michael
Abstract: The concept of national policy styles differs between states in respect of whether their governments react to policy changes in an anticipatory or reactive fashion and whether they seek to achieve consensus with societal actors or impose decisions on them. To date, this conceptualization has been applied to a limited number of states and produced only a small set of case studies due to the absence of large‐n data. We assess whether the dimensions on strategic planning and public consultation of the Bertelsmann Sustainable Governance Indicators (SGI) provide conceptually sound and empirically insightful indicators of national policy styles. Our explorative analysis reveals that the SGI are useful for operationalizing the concept of national policy styles and could advance the debate on it. Our analysis shows that differences exist between countries in terms of their policy styles, and that the policy styles remained stable in most countries between 2014 and 2020. 摘要: 国家政策风格 (national policy styles) 的概念在不同国家中存在差异, 具体表现为政府是否以预期性或反应性的方式响应政策变革, 以及政府是否试图与社会行动者达成共识或对其施加决策。迄今为止, 这一概念已被应用于一小部分国家, 并且仅产生了为数不多的案例研究 (因缺乏大样本数据) 。我们评估了可持续治理指标 (SGI) 的战略规划和公共咨询维度是否对国家政策风格提供理论健全且具有实证意义的指标。我们的探究性分析显示, SGI有助于对国家政策风格的概念进行操作化, 并且能促进相关辩论。我们的分析显示, 各国在政策风格上存在差异, 并且大多数国家在2014‐2020年间的政策风格保持稳定。 Resumen: El concepto de estilos de política nacional difiere entre estados con respecto a si sus gobiernos reaccionan a los cambios de política de manera anticipatoria o reactiva y si buscan lograr el consenso con los actores sociales o imponerles decisiones. Hasta la fecha, esta conceptualización se ha aplicado a un número limitado de estados y ha producido solo un pequeño conjunto de estudios de casos debido a la ausencia de datos de n grande. Evaluamos si las dimensiones sobre planificación estratégica y consulta pública de los Indicadores de Gobernanza Sostenible (SGI) proporcionan indicadores conceptualmente sólidos y empíricamente perspicaces de los estilos de política nacional. Nuestro análisis exploratorio revela que los SGI son útiles para operacionalizar el concepto de estilos de política nacional y podrían avanzar en el debate al respecto. Nuestro análisis muestra que existen diferencias entre los países en términos de sus estilos de política y que los estilos de política se mantuvieron estables en la mayoría de los países entre 2014 y 2020.